ANALISIS KINERJA KEUANGAN BANK UMUM PEMERINTAH TAHUN 2013 -2017 - Muhammad Hasan, Julian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The purpose of this study was to determine the effect of CAR, LDR, NIM and BOPO on ROA of Government Commercial Banks listed on the Indonesia Stock Exchange in the Blue Chip category for 2013-2017. The research design used in the preparation of this research is quantitative with descriptive explanations. The analysis method used is multiple linear regression analysis with a sample of 20 company data for the 2013-2017 period and the type of data used is time series. The results of the analysis show that CAR has a significant negative effect on ROA with a regression coefficient of -0.090. LDR has a positive but not significant effect on ROA with a regression coefficient of 0.076. NIM has a positive and significant effect on ROA with a regression coefficient of 0.487. BOPO has a negative and significant effect on ROA with a regression coefficient of -0.565. While the test results simultaneously show CAR, LDR, NIM and BOPO together have a significant effect on ROA with a coefficient of determination of 0.986